Learning Assessment With Portofolio - Nurhasan Nurhasan (Yayasan Ilomata, 2020)
To find out the competencies a person has, we need a tool called evaluation. There are two things that need to be distinguished in evaluation, the meaning is measurement and assessment or interpretation. To be able to measure correctly, you need the correct measurement tool too. The correct measuring device must meet several requirements, including: valid,reliable, and practical. There are several types of measuring devices. In addition there are subjective measurement tools (essays), objectives (multiple choice, matchmaking, short content, and right-wrong), and performance, now it is beginning to be known as portfolio measurement tools. The portfolio is a collection of the work of a student as a result of carrying out a performance task, which is determined by the teacher or by students with the teacher, as part of an effort to achieve learning goals, or achieve competencies specified in the curriculum. Key Word : Learning, Assessment, Portofolio